PENGGUNAAN BUKU KIA SEBAGAI MEDIA EDUKASI PADA IBU HAMIL (Studi di Wilayah Kerja Puskesmas Tlogosari Kulon, Tahun 2018) - Janet Pandora; Martha Irene Kartasurya; Sri Winarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The data coverage of MCH handbook ownership in Tlogosari Kulon Community Health Center is 95%, however, it is categorized as the first rank of maternal mortality cases in Semarang City. The objective of this study is to analyze the relationship between the use of MCH handbook with healthy practices of pregnant women in the work area of Tlogosari Kulon Community Health Center. This study was an explanatory research with cross-sectional design. The population in this study were 703 pregnant women with gestational age> 4 months. The subjects of the study were 93 pregnant women chosen by simple random sampling technique. The data analysis was by using spearman correlation test and Chi square. The results of the study shows that the knowledge of pregnant women with a good category (53.8%), the attitude of pregnant women with positive category (59.1%), healthy practice of pregnant women with a good category (58.1%), the use of MCH handbook with a good category (50.5%) and information from other sources with a good category (65.6%). There is no relationship between the use of MCH handbook with knowledge (p = 0.310), practice (p = 0.925) and there is a relationship of using MCH handbook with attitude (p = 0,000). Before they are controlled with information from other sources, it was found that there was no relationship between reading MCH handbook with knowledge (0.432), the healthy practice of pregnant women (0.797) and there is a relationship between reading the MCH handbook and the attitude of pregnant women toward health (0.000). After they are controlled with information from other sources, it obtains the same results. It is concluded that the use of MCH handbook only related to the attitude of pregnant woman toward health. It is suggested that existing programs need to be developed to support the use of MCH handbook as a health information by optimizing counseling and home visits by health workers.